Anti TNF-α therapy for ulcerative colitis: current status and prospects for the future. (4th March 2017) - Pugliese, Daniela; Felice, Carla; Papa, Alfredo; Gasbarrini, Antonio; Rapaccini, Gian Lodovico; Guidi, Luisa; Armuzzi, Alessandro
ABSTRACT: Introduction: Anti TNF-α agents have become a significant advance in the management of ulcerative colitis, proving to induce, with rapid onset, clinical and endoscopic remission. However, there is still a considerable unmet medical need in ulcerative colitis. Areas covered: The aim of this review was to summarize the patterns of use and the effectiveness of anti TNF-α in ulcerative colitis, highlighting their current position in treatment algorithms. Moreover, we set out a five-year view hypothesizing different treatment strategies. Expert commentary: The rapid onset of action and the effectiveness in inducing mucosal healing are the most important pros of anti TNF-α, supporting present and future use. Conversely, the relevant risk of loss of response and the safety profile have raised several concerns. In the future, the advent of different molecular targeting therapies can improve the management of UC patients, evolving to individually tailored strategies.